(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2026)
Classical Economic models (CEM) based on integer-order classical calculus commonly assume instantaneous market clearing and memoryless agent behavior. These assumptions frequently fail to account for the widespread reality of economic hysteresis, path dependency, and delayed responses. This study suggests for the incorporation of fractional calculus into economic dynamics as a more effective framework for describing such occurrences. We concentrate on the Conformable Fractional Derivative ( ), a contemporary fractional operator that preserves classical calculus’s basic concepts, such as the product, quotient, and chain rules, while adding an adjustable memory parameter. This characteristic makes it ideal for economic modeling. We reformulate foundational economic models, counting capital accumulation and price alteration components, utilizing . An expository arrangement to a fragmentary development show illustrates how a unitary subordinate arrange creates trends characterized by introductory dormancy and quickening development, adjusting more closely with watched financial behavior than its classical partner. The is displayed as an effective, however numerically tractable, device for upgrading the authenticity and prescient control of financial hypothesis.